2016
DOI: 10.1017/s1460396916000066
|View full text |Cite
|
Sign up to set email alerts
|

A focus group consultation round exploring patient experiences of comfort during radiotherapy for head and neck cancer

Abstract: Purpose: The aim of this study was to consult patients about their experiences of comfort while wearing a thermoplastic mask during head and neck radiotherapy before designing a study to develop a comfort scale for radiotherapy.Methods: A qualitative method using a focus group of patients receiving radiotherapy for head and neck cancer was deployed. Five patients were invited and agreed to participate. Semi-structured questions guided the focus group interview. Thematic analysis was used to identify themes.Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 21 publications
1
12
0
1
Order By: Relevance
“…Participants recalled a range of reactions to the mask and experienced different trajectories of mask-related distress during treatment. Consistent with previous studies (Clover et al, 2011;Goldsworthy et al, 2016), mask anxiety did not affect all participants. It appears some HNC patients appraise the mask as threatening whilst others do not.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Participants recalled a range of reactions to the mask and experienced different trajectories of mask-related distress during treatment. Consistent with previous studies (Clover et al, 2011;Goldsworthy et al, 2016), mask anxiety did not affect all participants. It appears some HNC patients appraise the mask as threatening whilst others do not.…”
Section: Discussionsupporting
confidence: 91%
“…A French study found that most participants did not experience mask-related anxiety and viewed the mask positively, as a 'protector' (Arino, Stadelmaier, Dupin, Kantor, & de Figueiredo, 2014). By contrast, other qualitative studies reported negative patient experiences and representations of the mask such as physical discomfort, claustrophobia and anxiety, difficulty coping and hating the mask (Goldsworthy, Tuke, & Latour, 2016;Molassiotis & Rogers, 2012). Given the diversity of the findings reported to date, this study aimed to explore the patient experience with immobilisation masks in the Australian and New Zealand settings.…”
mentioning
confidence: 97%
“…Należy rozważać komfort fizyczny, percepcję mentalną i bierność pacjenta przy doborze unieruchomień w codziennej praktyce radioterapeutycznej. Niemniej jednak najistotniejszy wpływ na poczucie komfortu dla pacjenta onkologicznego ma rozmowa z personelem medycznym [2]. W drugiej części sesji zwrócono uwagę na zastosowanie mechanicznej wentylacji w radioterapii nowotworów charakteryzujących się dużą ruchomością narządową.…”
Section: Najistotniejsze Wynikiunclassified
“…The PARiHS framework supports a codesign approach, where in-depth experiences of both HNC patients and the HPs who provide their care are documented and analysed [16]. Although HNC patients' mask-related experience has been explored in several qualitative studies [7,8,17], no study has explored the perspectives of HPs. Therefore, the present study aimed to elicit HPs' perspectives on the causes and experience of mask-related anxiety, the roles they and other HPs have in managing mask anxiety, potentially effective interventions and strategies for the person undergoing treatment, and perceived barriers and facilitators to implementing potential interventions within the health system.…”
Section: Introductionmentioning
confidence: 99%